Relative Contribution of Trabecular and Cortical Bone to Primary Implant Stability: An In vitro Model Study - Trinanjali Bera; Bhavna Jha Kukreja; Chetan Sharma; Vivek V. Gupta; Priya Patel; Parul Singhal; Manish S. Jadhav; Naina Pattnaik (Journal of Pharmacy and Bioallied Sciences)
Background: Primary implant stability is a crucial factor for the successful osseointegration and long-term success of dental implants. The contribution of trabecular and cortical bone to primary implant stability is not well understood. Materials and Methods: An in vitro model using synthetic bone blocks mimicking trabecular and cortical bone was used to simulate implant placement. The study involved 40 implants, divided into four groups based on bone type and density: Group A (low-density trabecular bone), Group B (high-density trabecular bone), Group C (low-density cortical bone), and Group D (high-density cortical bone). Primary stability was assessed using insertion torque values and resonance frequency analysis (RFA). Insertion torque was measured using a digital torque meter, and RFA was measured using an Osstell ISQ device. Results: Group D (high-density cortical bone) exhibited the highest insertion torque values (mean: 45 Ncm) and Implant Stability Quotient (ISQ) values (mean: 75), indicating superior primary stability. Group C (low-density cortical bone) showed moderate stability, with mean insertion torque values of 30 Ncm and ISQ values of 60. Group B (high-density trabecular bone) had lower stability, with mean insertion torque values of 25 Ncm and ISQ values of 55. Group A (low-density trabecular bone) demonstrated the least stability, with mean insertion torque values of 15 Ncm and ISQ values of 45. Conclusion: The study concludes that cortical bone, especially high-density cortical bone, significantly contributes to primary implant stability compared to trabecular bone. The findings suggest that bone quality should be a major consideration during implant placement to ensure optimal primary stability and long-term success.